Prevalence of chronic musculoskeletal pain and its associated factors towards treatment options among elderly in selected public clinics, Selangor, Malaysia - Lee, Foong Sim (2019)
Chronic pain is a highly prevalent disabling condition among older adults but little is known about its prevalence, the associated factors and also treatment option of preference among this population. Chronic pain of musculoskeletal origin is widespread among the elderly, which is often under-recognised and under-treated. The purpose of this study was to determine the prevalence and associated factors to treatment options for chronic musculoskeletal pain among the elderly in Petaling District, Selangor. A cross-sectional study was performed on 276 respondents recruited from six public health clinics in Petaling District, Selangor between August to September 2018. A stratified sampling proportionate to size with individual clinics as the strata was used in this study. Based on the proportion calculated from individual clinics, eligible elderly were selected by systematic random sampling based on the registration list. Data were collected using a pre-tested and validated questionnaire through face-to face interview with each respondent at the clinic. The questionnaire consisted of seven sections, namely, socio-demographic, comorbidity, depression, pain severity, treatment options, attitude towards chronic pain and chronic musculoskeletal pain. Data collected was analysed using IBM Statistical Package for Social Science (SPSS®) version 23.0. For data analysis, Chi-Square and Fisher’s Exact Tests were used to measure the association while predictors were examined using Multivariate Logistic Regression. The P value of < 0.05 regarded as statistically significant. A total of 276 respondents completed the questionnaires from 282 who were eligible, making the response rate of 97.9%. The findings of the study presented a high prevalence of chronic musculoskeletal pain among the elderly of 87.7%. The majority were treated with non-pharmacological treatment options for chronic musculoskeletal pain (85.1%), compared to only 44.6% for pharmacological treatment option and 37.3% treated with both. The predictive models revealed no significant factors found to be associated with the use of non-pharmacological treatment options. Stomach disease (AOR = 2.52, 95% CI [1.11, 5.75], P Value = 0.028), back pain (AOR = 2.59, 95% CI [1.40, 4.79], P Value = 0.002) and pain severity (AOR = 2.88, 95% CI [1.52, 5.45], P Value = 0.001) were found to be the significant factors associated with pharmacological treatment options; while back pain (AOR = 4.38, 95% CI [1.22, 15.69], P Value = 0.023) and presence of comorbidity (AOR = 4.2, 95% CI [1.30, 13.54], P Value = 0.016) were the significant factors associated with the use of both treatment options. This study showed a high prevalence of chronic musculoskeletal pain, which was dominated by non-pharmacological treatment options. Stomach disease, back pain and pain severity were associated with the adherence of respondents towards pharmacological treatment options while having back pain and presence of comorbidity were associated the use of both treatment options.